Safety and efficacy of a feed additive consisting of Bacillus subtilis FERM BP‐07462, Enterococcus lactis FERM BP‐10867 and Clostridium butyricum FERM BP‐10866 (BIO‐THREE®) for chickens for fattening, chickens reared for laying, turkeys for fattening, turkeys reared for breeding, all avian species for rearing/fattening to slaughter and all avian species reared for laying or breeding to point of lay (TOA BIOPHARMA Co., Ltd.). (16th June 2022) - ,; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of BIO‐THREE ® when used as a feed additive for chickens for fattening, chickens reared for laying, turkeys for fattening, turkeys reared for breeding, all avian species for rearing/fattening to slaughter and all avian species reared for laying or breeding to point of lay. The product under assessment is based on viable cells/spores of Bacillus subtilis FERM BP‐07462, Enterococcus lactis FERM BP‐10867 and Clostridium butyricum FERM BP‐10866. Based on the tolerance study provided, the Panel concluded that the additive is safe for the target species under the conditions of use. The additive is safe for the consumers of products derived from animals receiving the additive. The additive is not irritant to skin and eyes. The additive is a respiratory sensitiser. No conclusions could be drawn on its potential to be a skin sensitiser. The use of the product as a feed additive is of no concern for the environment. The FEEDAP Panel was not in the position to conclude on the efficacy of BIO‐THREE ® for the target species. BIO‐THREE ® is compatible with diclazuril, decoquinate and halofuginone. No conclusions could be drawn on the compatibility of BIO‐THREE ® with monensin sodium, salinomycin sodium, narasin, robenidine hydrochloride and maduramicin ammonium.